2020
DOI: 10.15419/bmrat.v7i10.637
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial cellulose-based aerogels for wound healing application: A review

Abstract: Aerogels have been steadily developed since its first invention to become one of the most promising materials for various medical and non-medical applications. It has been prepared from organic and inorganic materials, in pure forms or composites. Cellulose-based aerogels are considered one of the promising materials in biomedical applications due to their availability, degradability, biocompatibility and non-cytotoxicity compared to conventional silica or metal-based aerogels. The unique properties of such ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Similar finding have been gathered in previous studies, by using the aquas extract of J. mollissima ( Araújo et al, 2018 , de Queiroz Neto et al, 2019 ). Owing to the high content of many phytochemicals such as flavonoids, phenols, tannins and saponins, the extract exhibited strong antioxidant activity, which could be used as anticancer agent or in wound healing applications ( Abdul Khalil et al, 2020 , Goswami and Kuril, 2019 , Yahya et al, 2020a , Yahya et al, 2020b ). The results of hematological and biochemical analysis showed no significant variations between the control and treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding have been gathered in previous studies, by using the aquas extract of J. mollissima ( Araújo et al, 2018 , de Queiroz Neto et al, 2019 ). Owing to the high content of many phytochemicals such as flavonoids, phenols, tannins and saponins, the extract exhibited strong antioxidant activity, which could be used as anticancer agent or in wound healing applications ( Abdul Khalil et al, 2020 , Goswami and Kuril, 2019 , Yahya et al, 2020a , Yahya et al, 2020b ). The results of hematological and biochemical analysis showed no significant variations between the control and treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Sakai et al [ 41 ], the authors reported that supercritical drying of nanocellulose aerogel led to the generation of smaller and open pores compared with other drying approaches such as freeze-drying. Nanocellulose-based aerogels have been also utilized in medical applications due to their biocompatibility, noncytotoxicity, nonimmunogenicity and biodegradability; the past few years witnessed the use of such aerogels in drug delivery, tissue engineering, biosensing and wound dressing applications [ 42 , 43 , 44 ]. Nanocellulose-derived carbon aerogels are another form of aerogels that exhibit high adsorption capacity and are usually prepared by pyrolyzing the precursor materials [ 45 ].…”
Section: Nanocellulose-based Aerogels: Properties and Applicationmentioning
confidence: 99%
“…Surgical sutures made from conventional polymers have been reported to induce a certain degree of an undesirable inflammatory reaction upon using them in obstetric and gynecologic surgeries, which is different based on the used material [ 73 , 74 ]. Lee et al [ 75 ] evaluated the suture complication rates in addition to surgical outcomes of surgery (vaginal uterosacral ligament suspension) using synthetic polymers included monofilament polypropylene and multifilament polyester as sutures. The authors reported significant complications regarding using these synthetic polymers including suture erosion at the vaginal apex and granulation tissue, higher in multifilament polyester sutures [ 76 ].…”
Section: Health Impact Of Conventional Polymer-based Materials In mentioning
confidence: 99%